2012
DOI: 10.1186/1756-0500-5-575
|View full text |Cite
|
Sign up to set email alerts
|

Positive correlation between circulating cathelicidin antimicrobial peptide (hCAP18/LL-37) and 25-hydroxyvitamin D levels in healthy adults

Abstract: BackgroundTranscription of the cathelicidin antimicrobial peptide (CAMP) gene is induced by binding of the bioactive form of vitamin D, 1,25-dihydroxyvitamin D, to the vitamin D receptor. Significant levels of the protein hCAP18/LL-37 are found in the blood and may protect against infection and/or sepsis. We hypothesized that serum vitamin D levels may modulate the circulating levels of hCAP18. Only three studies have shown a positive correlation between circulating 25-hydroxyvitamin D and hCAP18 levels. Here … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
49
2
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(55 citation statements)
references
References 45 publications
(43 reference statements)
3
49
2
1
Order By: Relevance
“…As such, LL-37 may provide important first-line defense mechanisms for the innate immune system. 46 Prospective studies by members of our research group and others have shown maximal LL-37 expression to occur at 25(OH)D levels between 30 and 35 ng/mL, 47,48 thereby strengthening the biological basis for the association between higher 25(OH)D levels and optimal immune function.…”
Section: Discussionmentioning
confidence: 75%
“…As such, LL-37 may provide important first-line defense mechanisms for the innate immune system. 46 Prospective studies by members of our research group and others have shown maximal LL-37 expression to occur at 25(OH)D levels between 30 and 35 ng/mL, 47,48 thereby strengthening the biological basis for the association between higher 25(OH)D levels and optimal immune function.…”
Section: Discussionmentioning
confidence: 75%
“…A study conducted by Dixon et al in healthy adults identified a positive correlation between circulating plasma hCAP18/LL-37 and serum 25(OH) vitamin D in subjects with 25(OH) vitamin D levels ≤80 nmol/L as opposed to those with concentrations >80 nmol/L [28]. Bhan et al also found a positive correlation between serum 25(OH) vitamin D levels <80 nmol/l and baseline hCAP18/LL-37 levels, and changes in hCAP18/LL-37 levels after high-dose vitamin D 2 , ergocalciferol treatment [29].…”
Section: Discussionmentioning
confidence: 97%
“…Direct peptide application and over expression following gene therapy approaches have been precluded because of a number of significant toxicity issues (15-19). Additionally, direct administration of 1,25-hydroxyvitamin D 3 does induce hCAP 18 expression but low concentrations (10 −7 M 1,25-hydroxyvitamin D 3 ) generate cytotoxicity and led to the inhibition of cell growth (41-43). Other strategies are therefore needed to improve hCAP 18 expressions and LL-37 productions.…”
Section: Discussionmentioning
confidence: 99%